IN SILICO INVESTIGATION OF MOLECULAR INTERACTIONS BETWEEN INULOSUCRASE DERIVED FROM Aspergillus awamori AND EPE COMPOUNDS - Aini, Diah Miftahul; Fajriati, Elza Kamila; Yuanita, Emmy; Antari, Gladeva Yugi; Ratnasari, Baiq Desy; Damayanti, Eva Hikmatul (Tanjungpura University, 2025)
Fructooligosaccharides (FOS) are important prebiotics synthesized by the enzymatic activity of inulosucrase, and understanding their molecular interactions is essential for exploring potential modulators. This study examined the interaction between inulosucrase from Aspergillus awamori (PDB ID: 1Y4W) and the compound EPE (4-(2-hydroxyethyl)-1-piperazine ethanesulfonic acid) using an in silico molecular docking approach. Since the 1Y4W structure lacks a co-crystallized ligand, EPE was selected as a surrogate ligand derived from PDB ID: 3SC7 and prepared for docking simulations. Docking with AutoDock Vina produced a best binding affinity of